Exploring the severity and risk factors of non-alcoholic fatty liver disease using the SAF scoring system - Li, Xinxin; Wang, Shiyu; Zhang, Ziyu; Deng, Wen; Zhang, Yaqin; Cao, Weihua; Wei, Xin; Gao, Zixuan; Yao, Linmei; Wang, Shuojie; Yi, Wei; Xie, Yao; et al. (Frontiers in Medicine, 2025)
ObjectiveThe steatosis, activity, and fibrosis (SAF) score is a histological scoring system developed by the European Association for the Study of the Liver to evaluate liver biopsy samples in cases of non-alcoholic fatty liver disease (NAFLD). Based on histopathological results and SAF scores, NAFLD patients were categorized into mild, moderate, and severe groups. We compared the differences between these groups and identified the risk factors influencing lesion severity.MethodsWe gathered data from 539 NAFLD patients who underwent percutaneous liver biopsy confirmation at Beijing Ditan Hospital between January 2018 and December 2022. All biopsies were graded according to the SAF scoring system, and the severity of the disease was classified as mild, moderate, or severe. We compared the differences in gender, age, BMI, history of diabetes, history of hypertension, aspartate aminotransferase (AST), alanine aminotransferase (ALT), serum cholesterol levels, and other factors among NAFLD patients with varying degrees of disease severity. Additionally, we explored the risk factors that influenced the severity of lesions.ResultsA total of 539 patients were enrolled in this study, with ages ranging from 6 to 79 years. Among them, there were 325 men and 214 women in an average age of 39 ± 13 years. The patients were divided into three groups based on disease severity: mild NAFLD group (162 cases), moderate NAFLD group (210 cases), and severe NAFLD group (167 cases). The results showed significant differences between the three groups in terms of age composition, high-calorie diet, family history of hypertension, ALT, AST, GGT, total bile acids, cholinesterase, glycosylated albumin, blood glucose, uric acid, type III procollagen, serum human laminin, liver stiffness, and hepatic steatosis.ConclusionBMI, uric acid, AST, type III procollagen, liver stiffness, and hepatic steatosis play critical roles in the progression of NAFLD and contribute to high pathological SAF scores in NAFLD patients.